The Effects of Teacher Believes and Practice on Students’ Achievement of English Language Teaching - Husaini, Rizqi; Prasetiyowati, Eni (IREELL: Indonesian Review of English Education, Linguistics, and Literature, 2023)
Teachers’ beliefs are important for understanding and improving educational process. This is important because teachers believe is a guideline for the teacher to conduct or make the strategy in teaching learning process. It can shape learner’s learning environment, their motivation, and their learning achievement. The aims of this research to describe about what teachers believe about learning the language, whether there is a similarity between the teachers with other teachers. Secondly is about the influence from the teachers' beliefs about language learning with students' level of understanding of score taken either seen or directly to the confirmation on these students. And as a result, each teacher has a different understanding with other teachers. This is due to several factors other than the level of education is also on the material level and what is taught to students. Second, it also has an influence on the level of student understanding. Because teachers will use different approaches differ depending on what he believed and understood.